Impact of changes in anti-doping regulations (WADA guidelines) on asthma care in athletes - Couto, M.; Horta, L.; Delgado, L.; Capao-Filipe, M.; Moreira, A. (Clinical Journal of Sport Medicine, 2013)
Objective: To investigate how changes to the World Anti-Doping Agency (WADA) guidelines on asthma medication requests have impacted the management of asthmatic athletes in Portugal.